Transmission line overload alleviation due to contingency based on DAG assisted PSO method. (30th October 2009) - Maharana, Manoj Kumar; Swarup, K. Shanti
Transmission line overload initiate the cascading outages, which forces the system to collapse. The most practiced techniques for overload alleviation is generator rescheduling and/or load shedding. The appropriate selection of generators and load buses to perform the control action for overload alleviation is an important task for the operators. Local optimisation based overload alleviation requires appropriate selection of generator and load buses for minimum control action. This paper presents a new technique for selection of participating generators and load buses using direct acyclic graph (DAG). PSO solved the generator rescheduling and/or load shedding optimisation problem with in security constraints. The effectiveness of the proposed approach is demonstrated for different contingency cases in IEEE 30 and 57 bus systems. The result shows that the proposed approach is computationally fast, reliable and efficient, in restoring the system to normal state after a contingency with minimal control actions.